Sosialisasi dan Pelatihan Rain Water Harvesting (RWH) di SDN Meruya Utara 12, 13 Pagi dan 15 Petang - Fairus, Sirin; Surya Irawan, Diki; Nursetyowati, Prismita (LPkM Universitas Bakrie, 2020)
Rainwater is one of the potential clean water resources in urban areas, such as DKI Jakarta, which has not been used optimally. Related to this, community service activities had been carried out raising theme Rainwater Harvesting (RWH). This agenda was aimed to give education and understanding of RWH to teachers and students of SDN Meruya Utara 12, 13 Pagi and 15 Petang as one way how to conserve rainwater to provide clean water. These activities consisted of the socialization and installation of RWH in schools with a total capacity of 2000 L, where each 1000 L placed at the front of the school for hand washing and in the mosque for ablution purposes. Then agenda was continued with training how to work, to operate and to maintain the RWH equipment. The mass of collected rainwater was distributed into 2 filter tanks before entering the clean water supply tank and ready for use during the dry season. After the RWH had been tested, school residents could feel the benefits. It could reduce the volume of rainwater falling down from the roof of the school building and run-off that occured in the school area so as to avoid flooding. This instalation was able to provide sufficient clean water so that it could reduce the need for using groundwater for daily use. Through this program, school residents have understood the principles of work, how to operate, maintain and can benefit from this RWH.